Prophylactic RhCE and Kell antigen matching: impact on alloimmunization in transfusion‐dependent patients with myelodysplastic syndromes. Issue 1 (19th October 2016) - Lin, Y.; Saskin, A.; Wells, R. A.; Lenis, M.; Mamedov, A.; Callum, J.; Buckstein, R.
Abstract : Background and Objectives: Thirty to 80 per cent of patients with myelodysplastic syndromes (MDS) become transfusion‐dependent and are at risk for red blood cell (RBC) alloimmunization. This study compared alloimmunization rates in transfusion‐dependent patients with MDS at an institution with a policy of prophylactic antigen matching for RhCE and K (PAM) with those transfused at institutions without such a policy (non‐PAM). Materials and Methods: Transfusion records were retrospectively reviewed to determine total number of RBC transfusions received, whether RBC phenotyping was performed, the type and date of first alloantibody development and receipt of prophylactic antigen matching for RhCE and K. Results: In 176 transfusion‐dependent patients with MDS, the overall rate of new alloimmunization was 17%; the majority of patients (87%) developed at least one alloantibody to Rh or Kell antigens. The alloimmunization rate at the institution with a PAM policy was 11% compared with 23% at non‐PAM institutions ( P = 0·06). The rate of Rh/K alloimmunization was 7 vs. 22%, respectively ( P = 0·008). No patient who received PAM developed a Rh/K alloantibody. Conclusion: The rate of alloimmunization was 11% at an institution with a PAM policy which was non‐significantly lower than 23% at institutions without a PAM policy. However, rates of Rh/K alloimmunization were significantly lower. Such a policy should be considered in transfusion‐dependent patients with MDS, although further studies on cost‐effectiveness and careful consideration of resource availability in the local context are required.